Green Buildings and Sustainable Engineering Proceedings of GBSE 2018 - Drück, Harald; Pillai, Radhakrishna G.; Tharian, Manoj G.; Majeed, Aysha Zeneeb; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises the proceedings of the International Conference on Green Buildings and Sustainable Engineering (GBSE 2018), which focused on the theme "Transforming our Built Environment through Innovation and Integration towards a Smart and Sustainable Future". The papers included address all aspects of green buildings and sustainability practices in civil engineering, and offer a valuable reference resource for researchers, practitioners, and policy makers. .
CONFERENCE TRACKS: Green Buildings -- Smart Energy Systems -- Green Manufacturing & Materials -- Nanotechnology for Environmental Remediation and Protection -- Sustainable Energy Technologies -- Energy Storage Technology and Materials -- Life Cycle Analysis and Sustainability Assessment of Materials and Products -- Recycling and Waste Management -- Security of Energy Supply -- Ecological Liveable Environment Construction -- Sustainable Traffic Solutions including e-mobility -- Effective Water Management Systems -- Sanitation and Waste Water Management -- Architectural Concepts for Smart Cities including Advanced Tools such as GIS -- Environmental Geotechnics -- Ground Improvement Techniques.
Keywords: Sustainable architecture; Buildings -- Design and construction; Sustainability; Sustainable Architecture/Green Buildings; Building Construction and Design; Sustainability